Use of Heated Humidified Gases for Early Stabilization of Preterm Infants: A Meta-Analysis - Meyer, Michael P.; Owen, Louise S.; te Pas, Arjan B. (Frontiers in Pediatrics, 2018)
Background Large observational studies in preterm infants have shown an increase in mortality and morbidity when admission temperature is below 36.5°C. Recent randomized controlled studies showed a reduction in admission hypothermia and an increase in the number admitted with normal temperature (36.5 to 37.5°C) when heated humidified gases were used for initial stabilization. Objective The goal of this study was to perform a meta-analysis of published randomized trials using heated humidified gas compared to cold dry gas in preterm infants immediately after birth and during transport to the neonatal unit. Specific research aims were to determine the magnitude of the reduction in hypothermia and to examine neonatal outcomes including mortality. Methods A literature search was conducted in accordance with the standard methods of the Cochrane Neonatal Work Group. Randomized trials were identified and data entered into RevMan5. A fixed effects statistical model was used. Risk of bias was assessed for included studies and the GRADE approach used to determine quality of evidence. The primary outcome was admission hypothermia (<36.5°C). Secondary outcomes included admission temperature in the normothermic range (36.5-37.5°C) and neonatal outcomes including mortality. Results Two studies met inclusion criteria and 476 preterm infants <32 weeks were enrolled. Studies were not blinded but the overall risk of bias was low. Admission hypothermia was reduced by 36% (CI 17-50%), and admission normothermia significantly increased. GRADE quality of evidence was high for these outcomes. The number of infants with more severe hypothermia ( <35.5°C) was significantly reduced (RR 0.32 CI 0.14-0.73). Preterm infants <28 weeks had significantly less admission hypothermia (RR 0.61 CI 0.42, 0.90). Mortality and respiratory outcomes were not significantly different (studies were not powered for these outcomes), though there was a trend to improvement in all respiratory measures assessed. There were no significant adverse events and no increase in admission hyperthermia (>37.5°C). Conclusions Heating and humidification of inspired gases immediately after birth and during transport to the neonatal unit improves admission temperature in preterm infants. Consideration should be given to incorporating this technique into other strategies (eg use of plastic wrap) designed to keep preterm infants warm on admission.